Tax Incentives in The Philippines : A Regional Perspective - Chalk, Nigel (IMF Working Papers; Working Paper ;, 2001)
The Philippines is faced with a policy dilemma in the area of corporate taxation. On the one hand, the country has, over the past few years, witnessed a decline in revenue as a share of output. On the other, it is operating in an increasingly competitive regional market for foreign direct investment. In order to remain competitive, the Philippines offers a broad array of fiscal incentives to entice inward investment and pursue the country's development goals. This paper looks at the fiscal incentives available in the Philippines, compares them with those available in the ASEAN region, and with the evidence on the efficacy of tax incentives in a global context. The paper provides some broad conclusions on the use of the various forms of tax incentives in the Philippines and on their administration.